ANALISIS PERAN KOPERASI SYARIAH BAGI MASYARAKAT - Faiz Qadri Sahri Lubis; Khusnul Ashar (Islamic Economics and finance in Focus, 2024)
This research aims to determine the role of sharia cooperatives in improving welfare and the mechanism for distributing productive financing to the community, especially traders around the Medan Tasbih Complex. The research method used is descriptive analytical research using data collection through field observation, interviews and documentation. The results of this research show that the BMT Al-Musabbihin sharia cooperative has provided many benefits for the community to gain prosperity and be free from the detrimental practice of usury and reduce the dependence of small traders from financial institutions on conventional banks and loan sharks. The BMT AL Musabbihin sharia cooperative has played a role in providing business credit to increase business capital through savings and loan credit, namely providing investment capital to its members, especially among Small and Medium Enterprise (SME).